Some Fundamental Aspects of Mechanics of Nanocomposite Materials and Structural Members - Alexander N. Guz; Jeremiah J. Rushchitsky (Journal of Nanotechnology)
This paper is devoted to formulation and analysis of fundamental aspects of mechanics of nanocomposite materials and structural members. These aspects most likely do not exhaust all of the possible fundamental characteristics of mechanics of nanocomposite materials and structural members, but, nevertheless, they permit to form the skeleton of direction of mechanics in hand. The proposed nine aspects are described and commented briefly.